Detection of Amyloid β Signature in the Lens and Its Correlation in the Brain to Aid in the Diagnosis of Alzheimer's Disease. (December 2015) - Kerbage, Charles; Sadowsky, Carl H.; Tariot, Pierre N.; Agronin, Marc; Alva, Gustavo; Turner, F. Darell; Nilan, Dennis; Cameron, Anne; Cagle, Gerald D.; Hartung, Paul D.
We report the findings from a clinical trial in which a group of patients clinically diagnosed with probable Alzheimer's disease (AD) were discriminated from an age-matched group of healthy volunteers (HVs) with statistical significance ( P < .001). The results from 20 patients with AD and 20 HVs were obtained by a Fluorescent Ligand Eye Scanning (FLES) technique that measures a fluorescent signature specific to an exogenous ligand bound to amyloid-β in the lens of the eye. Sensitivity and specificity of 85% and 95%, respectively, have been achieved in predicting clinical diagnosis. Additionally, amyloid brain imaging using florbetapir F18 positron emission tomography shows significant correlation with the results obtained in the eye. Results of the study demonstrate the safety of the FLES system.